Implementasi Kebijakan Akses Fulltext Karya Ilmiah Dosen pada Repositori Institusi Sekolah Tinggi Agama Islam Negeri (STAIN) Pamekasan - Cahyono, Hairul Agust (Universitas Wijaya Kusuma Surabaya, 2019)
The demands of the users are answered by educational institutions and institutional libraries in particular by organizing institutional repositories. The STAIN Pamekasan Library has organized an institutional repository that applies the full-text access policy but is still limited to lecturers' scientific work only. Research problems were identified by researchers in four (4) things, namely how the lecturers 'knowledge of institutional repositories, how to upload the STAIN Pamekasan Library institutional repository, how the benefits and obstacles experienced by lecturers when accessing institutional repositories and the implementation of full-text access to lecturers' scientific work on repositories STAIN Pamekasan Library institution which is also a formulation of research problems. The research approach used was descriptive qualitative, with informants as many as 9 (nine) lecturers, three of whom were also high-ranking institutional officials. The results showed that the lecturers' knowledge and understanding were still lacking due to the lack of socialization of the existence of institutional repositories, the two uploading processes felt by the lecturers were not complicated but lack of support for the third scientific upload guide for the STAIN Pamekasan Library institution. The problem formulation concluded that almost all STAIN Pamekasan lecturers agreed to the implementation of the policy of accessing full-text scientific work to lecturers at the institutional repository of the STAIN Pamekasan Library.